HUMAN CAPITAL INVESTMENT ON INDUSTRIAL PRODUCTIVITY IN INDONESIA - Faisol -; Suhardi - (UNEJ e-Proceeding)
The manufacturing industry is the largest sector in contributing to GDP in Indonesia. In the last four years showed that although the amount of output of manufacturing industry sector from year to year tends to increase, but the problem when viewed from the empirical data percentage of growth in the contribution of the manufacturing sector in Indonesia tend to be decreased. In long term is expected to increase the effectiveness of human resources, which in turn will lead to greater corporate performance is good performance of financial and non-financial performance, all of which will increase the gross domestic product as a measured key in rising per capita income of a country. The aim of this study is to test empirically the impact of human capital investment that is interpreted by education level and other variables both short and long term to productivity of Manufacturing Industry in Indonesia. This research data is secondary data published by World Bank and International Financial Statistic (IFS) for the period 1984-2014. The analyze method is using the Engle-Granger approach Co-integration and Error Correction Model (ECM). The first Stage test is Stationer test. The Co-integration test and ECM Test From the estimation results indicate that the relationship between Human Capital to the growth of manufacturing industry value added (IMVA). In the estimation equation of short-term and long-term human capital in the proxy with the level of education at the primary level (Pri) and secondary level (Sec) significant positive effect on the growth of value-added manufacturing industry in Indonesia. The long-term equation estimation results also show that the gross capital formation (GCF), labor force (LBF), enrollment in primary (Pri), and enrollment in secondary (Sec) variables have a positive effect on the productivity of Indonesia's manufacturing industry as reflected by Value added industrial manufacturing (IMVA). While the enrollment in tertiary and GDP variables have no significant effect on IMVA in the long term